2020
DOI: 10.1029/2019wr026272
|View full text |Cite
|
Sign up to set email alerts
|

CSO Reduction by Integrated Model Predictive Control of Stormwater Inflows: A Simulated Proof of Concept Using Linear Surrogate Models

Abstract: Combined sewer overflows (CSO) of mixed stormwater and wastewater pollute nearby receiving surface waters and pose a risk to the environment and human health. We use “integrated stormwater inflow control” to mitigate CSO by dynamically controlling the inflow of stormwater to the combined sewer system in real time, expanding the physical space of traditional real‐time control. This control is carried out with model predictive control (MPC), which we base on convex optimization including a linear internal surrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The CSO and flooding volume are affected by the diversity of rainfall events, even under the same CSS (Lund et al, 2018(Lund et al, , 2020van Daal et al, 2017). Thus, they might not be objective enough to measure the performance of RLs.…”
Section: The Index For Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The CSO and flooding volume are affected by the diversity of rainfall events, even under the same CSS (Lund et al, 2018(Lund et al, , 2020van Daal et al, 2017). Thus, they might not be objective enough to measure the performance of RLs.…”
Section: The Index For Uncertainty Analysismentioning
confidence: 99%
“…Model predictive control (MPC), one of the widely studied optimization‐based methods, uses internal UDS model, rainfall forecasts, and optimization algorithm to recursively calculate optimal control action, and thus, achieves better adaptability and performance compared with HC (Fu et al., 2008; Joseph‐Duran et al., 2015; Lund et al., 2020; Schütze et al., 2002; Sun et al., 2020). It consists of receding horizon principle and optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The model predictive control (MPC), a representative method of the optimization‐based approaches, uses an internal UDS model and real‐time rainfall forecasts to recursively compute optimal control variables on receding horizons and, thus, avoids the drawbacks of the heuristic methods. However, it is constrained by the computation time of the real‐time optimization and the accuracy of the rainfall forecast (Lund et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The state-of-the-art in research has demonstrated that a reduced complexity approach to CSO modelling can be used to create accurate simulations in a fraction of the time (Nielsen et al, 2007;Morales et al, 2017). This enables modelling of CSOs in contexts that require rapid simulations, for example, Lund et al (2020) use surrogate modelling to control CSO behaviour with optimisation of Model Predictive Control (MPC). These studies all employ some form of spatial aggregation to achieve the reduction in complexity.…”
Section: Introductionmentioning
confidence: 99%